Transcriptomic Analysis of Toxoplasma Development Reveals Many Novel Functions and Structures Specific to Sporozoites and Oocysts - Fritz, Heather M.; Buchholz, Kerry R.; Chen, Xiucui; Durbin-Johnson, Blythe; Rocke, David M.; Conrad, Patricia A.; Boothroyd, John C. (PLOS ONE, 2012)
Sexual reproduction of Toxoplasma gondii occurs exclusively within enterocytes of the definitive felid host. The resulting immature oocysts are excreted into the environment during defecation, where in the days following, they undergo a complex developmental process. Within each oocyst, this culminates in the generation of two sporocysts, each containing 4 sporozoites. A single felid host is capable of shedding millions of oocysts, which can survive for years in the environment, are resistant to most methods of microbial inactivation during water-treatment and are capable of producing infection in warm-blooded hosts at doses as low as 1–10 ingested oocysts. Despite its extremely interesting developmental biology and crucial role in initiating an infection, almost nothing is known about the oocyst stage beyond morphological descriptions. Here, we present a complete transcriptomic analysis of the oocyst from beginning to end of its development. In addition, and to identify genes whose expression is unique to this developmental form, we compared the transcriptomes of developing oocysts with those of in vitro-derived tachyzoites and in vivo-derived bradyzoites. Our results reveal many genes whose expression is specifically up- or down-regulated in different developmental stages, including many genes that are likely critical to oocyst development, wall formation, resistance to environmental destruction and sporozoite infectivity. Of special note is the up-regulation of genes that appear “off” in tachyzoites and bradyzoites but that encode homologues of proteins known to serve key functions in those asexual stages, including a novel pairing of sporozoite-specific paralogues of AMA1 and RON2, two proteins that have recently been shown to form a crucial bridge during tachyzoite invasion of host cells. This work provides the first in-depth insight into the development and functioning of one of the most important but least studied stages in the Toxoplasma life cycle.